Exome sequencing identifies NMNAT1 mutations as a cause of Leber congenital amaurosis - Chiang, Pei-Wen; Wang, Juan; Chen, Yang; Fu, Quan; Zhong, Jing; Chen, Yanhua; Yi, Xin; Wu, Renhua; Gan, Haixue; Shi, Yong; Chen, Yanling; Barnett, Christopher; et al. (Nature genetics, 2012)
Ming Qi and colleagues report that compound heterozygous mutations in NMNAT1 cause Leber congenital amaurosis, a childhood form of retinal dystrophy. NMNAT1 encodes an enzyme previously implicated in protection against axonal degeneration. Leber congenital amaurosis (LCA) is an autosomal recessive retinal dystrophy that manifests with genetic heterogeneity. We sequenced the exome of an individual with LCA and identified nonsense (c.507G>A, p.Trp169*) and missense (c.769G>A, p.Glu257Lys) mutations in NMNAT1 , which encodes an enzyme in the nicotinamide adenine dinucleotide (NAD) biosynthesis pathway implicated in protection against axonal degeneration. We also found NMNAT1 mutations in ten other individuals with LCA, all of whom carry the p.Glu257Lys variant.